The Phospholipid System with the Targeted Peptide Angiopep-2 for Delivery of Chlorine e6 an in vitro Study - Tereshkina, Y.A.; Kostryukova, L.V.; Pyatigorsky, A.M.; Tikhonova, E.G. (Biomedical Chemistry: Research and Methods, 2024)
The previously obtained phospholipid nanosystem for the delivery of the photosensitizer chlorine e6 was modified with a targeting ligand, the oligopeptide angiopep-2, exhibiting a high ability to transcytose through the blood-brain barrier. This feature of angiopep-2 is especially relevant for the targeted delivery of therapeutic and diagnostic agents to pathological area (tumor) of the brain. According to the analysis of the physico-chemical parameters of the developed composition, the particle size was 31.98±1.98 nm (PdI 0.453±0.03), the ζ-potential corresponded to -27.43±1.14 mV, while the substance was almost completely (98.6±0.43%) incorporated into nanoparticles. An in vitro experiment on the human glioblastoma cell line U-87 MG showed an increase in the total accumulation and internalization of chlorine e6 in the variant with the phospholipid form containing the targeted peptide compared with the free substance by 33% and 40%, respectively. The study of the cytotoxic action without irradiation showed no differences between the samples in the concentration range from 0.125 μg/ml to 2.5 μg/ml (in terms of to chlorine e6); the percentage of living cells was about 100%. The study of the photoinduced activity (with a dose 1,5 J/cm2 irradiation) showed that the IC50 value for the obtained composition was 1,33 times lower than that for the free substance and amounted to 2.85±0.1 μg/ml. The results of the experiments suggest the prospects of the developed composition and the clear need for further studies in vitro and in vivo.